TEST IMPACT: ENGLISH CERTIFICATION EXIT REQUIREMENTS IN TAIWAN - Yi-Ching Pan (TEFLIN Journal: A publication on the teaching and learning of English, 2009)
Abstract: In light of the importance of understanding the social impacts of test use, this paper synthesizes the opinions and surveys of a variety of stakeholders, including businesses, the government, administrators, educators and students, regarding the English exit requirements, as reported in major local newspapers during the last decade.ÃÂ  It then constructs implications in terms of considerations for those involved in the establishment of the requirements and provides insights and suggestions for other stakeholders.ÃÂ  By doing so, it is hoped that this study will be beneficial to those who are active in the fields of English teaching, policy-making and test development.